2010
DOI: 10.1021/es903853v
|View full text |Cite
|
Sign up to set email alerts
|

Physical Modeling of Air Flow During Air Sparging Remediation

Abstract: Air sparging (AS) is one of the most efficient techniques for remediating saturated soils and groundwater contaminated with volatile organic compounds. A series of physical modeling tests for different sizes of porous media under varied injection pressure were conducted to investigate the effect of particle size and air injection pressure on size and shape of the zone of influence (ZOI). The test results show that ZOI can be expressed by two components: the horizontal expansion due to pneumatic fracture or pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…It is well known that the remediation efficiency is primarily affected by the gas flow patterns, which are often categorized as channel flow, slug flow, or bubble flow [Brooks et al, 1999;Chen et al, 1996;Elder and Benson, 1999;Hu et al, 2010]. When gas is transported continuously, channel flow may occur.…”
Section: Air Spargingmentioning
confidence: 99%
“…It is well known that the remediation efficiency is primarily affected by the gas flow patterns, which are often categorized as channel flow, slug flow, or bubble flow [Brooks et al, 1999;Chen et al, 1996;Elder and Benson, 1999;Hu et al, 2010]. When gas is transported continuously, channel flow may occur.…”
Section: Air Spargingmentioning
confidence: 99%
“…Based on the centrifuge tests employing glass beads as soil, Hu et al [40,41] simulated the air sparging under a wide range of sparging pressures and centrifuge g levels. Four samples with different particle size distribution were prepared and tested under different g -levels of 15, 30, 40 and 50.…”
Section: In-situ Remediation Of Gasolinementioning
confidence: 99%
“…The available oxygen in the groundwater environment could be increased by introducing oxygen into the aquifer by sparging with air, pure oxygen or ozone and by the addition of H 2 O 2 or oxygen-releasing compounds. [10,11] Use of H 2 O 2 is a cost-effective approach that is attracting increased attention, because it is soluble in water and provides unlimited amounts of oxygen for biodegradation. Mukherjee et al have shown that the accretion of 0.01% (v/v) H 2 O 2 as an additional source of oxygen in the culture medium containing Bacillus subtilis DM-04 and Pseudomonas aeruginosa strains remarkably enhanced the biodegradation rate of benzene, toluene and three xylene isomers under oxygen-limited conditions.…”
Section: Introductionmentioning
confidence: 99%